2020
DOI: 10.1016/j.heliyon.2020.e04669
|View full text |Cite
|
Sign up to set email alerts
|

Co-application of biochar and titanium dioxide nanoparticles to promote remediation of antimony from soil by Sorghum bicolor: metal uptake and plant response

Abstract: Association of titanium dioxide nanoparticles (TiO 2 NPs) and biochar (BC) to assist phytoremediation of Sb contaminated soil was investigated in this study. Seedlings of Sorghum bicolor were exposed to different regimes of TiO 2 NPs (0, 100, 250 and 500 mg kg −1 ) and BC (0, 2.5% and 5%), separately and in combination, to investigate the effects on plant growth, Sb absorption and accumulation and physiological response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 61 publications
(88 reference statements)
2
6
0
1
Order By: Relevance
“…3). Similar findings were reported by Zand et al (2020), i.e. significant increases in sorghum biomass were observed in a Sb-contaminated soil with increasing biochar rates (e.g., 0, 2.5 and 5%).…”
Section: S Vulgare Growth In Pte-contaminated Soil: Influence Of Bioc...supporting
confidence: 89%
See 2 more Smart Citations
“…3). Similar findings were reported by Zand et al (2020), i.e. significant increases in sorghum biomass were observed in a Sb-contaminated soil with increasing biochar rates (e.g., 0, 2.5 and 5%).…”
Section: S Vulgare Growth In Pte-contaminated Soil: Influence Of Bioc...supporting
confidence: 89%
“…Also, Ningyu et al (2016) reported a high PTE absorption efficiency of S. vulgare and showed that Pb, Cd and Zn were particularly accumulated in the roots. Finally, Zand et al (2020) detected high Sb accumulation in the aboveground parts of S. vulgare, supporting its use for Sb phytoextraction in contaminated soils. All this experimental evidence suggests that sorghum plants have promising phytostabilisation and/or phytoextraction potentials which overall depend on soil physico-chemical properties, PTE type, and concentration.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, low mobility in the soil may impact its absorption by plants [72]. Our results showed that the root accumulation of TiO 2 NPs was higher than that of stems and shoots, indicating that bamboo roots prefer to be storage organs of titanium, which has been reported in another study [73]. Therefore, the accumulation of titanium NPs led to the adsorption of heavy metals in roots, which, as a physical barrier, reduces metal translocation from roots to shoots.…”
Section: Discussionsupporting
confidence: 66%
“…According to those authors, the reason is that the absorption of NPs by roots is influenced by factors such as size, surface load, shape, exposure time of NPs, evaluated plant species, root conditions, and rhizosphere processes (Lv et al 2019;Singh and Kumar 2020). Studies reported by Daryabeigi Zand et al (2020) demonstrated that concentrations of 500 mg TiO 2 NPs kg −1 of dry soil affected the height and size of roots of Sorghum bicolor (L.) Moench in soil with a pH of 7.7. According to the authors, due to photocatalytic activities, TiO NPs can induce adverse effects on plants and can be related to the damage caused to the microbial community of the rhizosphere.…”
Section: Effects Of Tio 2 Nps On Morphological Characteristics In Zea Maysmentioning
confidence: 99%